TRANSFORMATIONAL LEADERSHIP: A LITERATURE REVIEW OF CONCEPTS, TRENDS, AND FUTURE RESEARCH DIRECTIONS - Firdaus; Aditya Putri, Metha; Johannes (Qawwam : The Leader's Writing, 2025)
This research aims to identify and analyze thematic, methodological, and research gaps in the study of transformational leadership over the past two decades. The method used is Systematic Literature Review (SLR) with the PRISMA approach, which selects 20 articles from internationally reputable journals indexed by Scopus. Data are collected and analyzed based on research focuses, methods, and key findings related to the influence of transformational leadership on performance, innovation, organizational culture, and employee engagement. The results of the study show that transformational leadership consistently contributes positively to improving individual and organizational performance through mediation mechanisms such as trust, organizational learning, and knowledge management. However, previous research still shows limitations in contextual aspects, especially in the areas of leadership digitalization, organizational culture differences, and longitudinal research design. This study recommends that future research integrate cross-cultural and multi-method approaches to broaden understanding of transformational leadership dynamics in the digital age. Practically, the results of this research contribute to the development of leadership strategies that are adaptive, innovative, and oriented towards human resource empowerment in the context of modern organizations.